Performance and emission characteristics of a compression ignition (CI) engine operated with beauty leaf biodiesel. (February 2019) - Bhuiya, Muhammad; Rasul, Mohammad; Khan, Mohammad; Ashwath, Nanjappa
Abstract: In this investigation, diesel and beauty leaf ( Calophyllum inophyllum L.) biodiesel (BLB)-diesel blends (B5, B10 and B20) were used to evaluate the performance and emission characteristics of a compression ignition (CI) engine. During the experiment, the speed of the engine was varied from 1200 rpm to 2400 rpm at 200 rpm interval. The results indicated that the performance characteristics, such as BP and BSFC in biodiesel blended fuel increases with increase in engine speed at full load condition with a few exceptions in BSFC at 1400 rpm. On the other hand, BTE and BMEP in biodiesel blended fuel decreases with increase in engine speed at 100% load with few exceptions at 1400 rpm. The results also revealed that the BP, BTE and BMEP are lower, whereas, the BSFC is higher in biodiesel blended fuel in comparison to diesel. In terms of emission characteristics, the results indicated that the emission of nitrogen oxides (NOx) increases, whereas, carbon monoxide (CO), hydrocarbon (HC), and particulate matter (PM) decreases with increase in engine speed at full load condition. The results also shown that the use of biodiesel-diesel blends in CI engine led to the significant reduction in CO, HC and PM emissions in comparison to conventional diesel. On the other hand, it has been observed that the NOx emissions are increased in biodiesel-diesel blends when they are compared to diesel.